Training on the Introduction of TOEFL (Test of English as Foreign Language) to High School Students in Bandung - Levita Dwinaya; Corry Caromawati; Nur Fitrianti Fahrudin; Sofia Umaroh; Arni Sukmiarni (REKA ELKOMIKA: Jurnal Pengabdian kepada Masyarakat, 2022)
The Test of English as a Foreign Language (TOEFL) is a type of language test of which results are often used as a reference for new student admission in Universities. However, this test is not included in the English language learning curriculum at the secondary level so high school students are not familiar with it. Therefore, this community service activity aims at introducing the test to middle-level students so that they have knowledge and are familiar with the types of questions tested in this test. To determine the progress of students' knowledge and abilities, pre and post-tests were conducted, and the result was the improvement of the scores indicating that the learning approach chosen in this activity is in accordance with the objective of the training. In addition, a simple information system for test assessment was created using Microsoft Excel. This information system helps record student grades and makes it easier to convert TOEFL scores.